Characterization and antifungal properties of oil palm mesocarp fiber superheated steam condensate - Sharip, Nur Sharmila (2016)
Degradation of hemicellulose, low molecular weight lignin and some amount of cellulose during pretreatment of lignocellulose by steam treatment produces acids, furans and phenolic compounds. These compounds are known to have antimicrobial properties. It has been recently reported that superheated steam (SHS) can be used as pretreatment method to alter the structure of lignocellulose prior to bioconversion or biocomposite production. Since SHS is a dry steam, the mechanism of lignocellulose degradation is unclear and hence its degradation products are unknown. Hence this study was conducted, with the aim to characterize the condensate from SHS treatment of oil palm mesocarp fiber (OPMF) and subsequently evaluating the effect of SHS treatment temperature on antifungal properties of the condensate. Results showed that OPMF condensate obtained (OS sample) was light yellowish-brown in colour with average pH of 3.04 ± 0.02. Detailed chemical compositional study by GCMS showed the presence of two different groups of compounds, with phenolic groups showed the most intense composition compared to the others. HPLC analysis showed that four types of carboxylic acids were generated during SHS treatment and formic acid was found as the most concentrated acid in the condensate (657 mg/L). Meanwhile, the concentrated OS sample (labeled as RF fraction) contained higher number of compounds (62 compounds), which were classified into ten different groups. Furthermore, the chemical composition of the condensates were exponentially increased by increases of SHS temperature; from 200ºC to 240ºC, while no significant increment was seen from 190ºC to 200ºC. This is in consistent with lignocellulose thermal degradation temperature. RF fraction of samples obtained from SHS treatment at 240°C showed 5.5 ± 0.17, 5.2 ± 0.1 and 8.0 ± 0.4 inhibition ratios on Bacillus cereus, Escherichia coli and Staphylococcus aureus, respectively. For fungal species, growth inhibitory test by agar dilution method showed that the growth of Aspergillus fumigatus UPM2 and Trichoderma asperellum UPM1 were suppressed by 51.8%, and 45.5%,correspondingly. This is supported by spore germination inhibition whereby no germination of spore was seen for both fungi tested. It is interesting to note that the OPMF condensate managed to fully inhibit the growth of Ganoderma boninense UPM13, which is a type of fungus causing basal stem rot (BSR) disease at the oil palm plantation. Results obtained herewith are very interesting as at present there is lack of information on the chemical composition of steam condensate obtained from SHS treatment of lignocellulose. The inhibitory effect of the OPMF SHS condensate on the growth of G. boninense UPM13 is indeed a new insight and should be used as a basis for future study on the development of antifungal agent for combating BSR disease.